Effects of process parameters on the physicochemical properties of corn stalk hydrochar and the removal of alkali and alkaline earth metals. Issue 7 (20th January 2021) - Yang, Li; Wang, Hui; Sun, Jianwei; Xu, Yiyun; Li, Pengcheng; Xu, Youning; Wu, Shaohua
Abstract: The advantages of the direct combustion of agricultural biomass for power generation are restricted due to the drawbacks of this biomass and the deep peak shaving trend. Hydrothermal carbonization can improve the physical and thermochemical properties of raw materials. Corn stalk samples were selected as the research object in this study. Corn stalk hydrochars were prepared with reaction pressures of 0–3 MPa, reaction temperatures of 160–240 °C, and residence times of 1–10 h. The effects of the process parameters on the physicochemical properties of hydrochar and on the removal of alkali and alkaline earth metals (AAEMs) were studied by measuring the hydrochar mass, energy yield, product composition, morphology, as well as the removal efficiency of AAEMs. The results indicated that the corn stalk hydrochar had higher mass and energy yields than the raw corn stalk. X‐ray diffraction showed that the carbon content in the hydrochar was greater than that in raw corn stalk. Scanning electron microscopy showed that the reaction temperature played a more significant role in the hydrothermal carbonization process than the reaction pressure and residence time.